2013
DOI: 10.1021/ja402456b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Nanoelectrodes: Fabrication and Size-Dependent Electrochemistry

Abstract: The fabrication and electrochemistry of a new class of graphene electrodes are presented. Through high-temperature annealing of hydrazine-reduced graphene oxides followed by high-speed centrifugation and size-selected ultrafiltration, flakes of reduced graphene oxides (r-GOs) of nanometer and submicrometer dimensions, respectively, are obtained and separated from the larger ones. Using n-dodecanethiol-modified Au ultramicroelectrodes of appropriately small sizes, quick dipping in dilute suspensions of these sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 114 publications
5
91
0
3
Order By: Relevance
“…Although it was suggested that the higher k 0 for Ru(NH 3 ) 6 3+/2+ on Pt compared to macroscopic electrodes could be due to diffuse double layer (Frumkin) effects, which may be more pronounced on nanoscale electrodes, 78 it is interesting to note that the highest reported k 0 values for Ru(NH 3 ) 6 3+/2+ on distinctly different electrodes are -in fact -rather similar, e.g. 10 ± 5 cm s -1 on metallic single walled carbon nanotubes, 49 9 cm s -1 on the basal surface of HOPG (free from defects), 8 9 -10 cm s -1 on reduced graphene oxide, 78 13.5 ± 2 cm s -1 on Au and 17.0 ± 0.9 cm s -1 on Pt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was suggested that the higher k 0 for Ru(NH 3 ) 6 3+/2+ on Pt compared to macroscopic electrodes could be due to diffuse double layer (Frumkin) effects, which may be more pronounced on nanoscale electrodes, 78 it is interesting to note that the highest reported k 0 values for Ru(NH 3 ) 6 3+/2+ on distinctly different electrodes are -in fact -rather similar, e.g. 10 ± 5 cm s -1 on metallic single walled carbon nanotubes, 49 9 cm s -1 on the basal surface of HOPG (free from defects), 8 9 -10 cm s -1 on reduced graphene oxide, 78 13.5 ± 2 cm s -1 on Au and 17.0 ± 0.9 cm s -1 on Pt.…”
Section: Discussionmentioning
confidence: 99%
“…10 ± 5 cm s -1 on metallic single walled carbon nanotubes, 49 9 cm s -1 on the basal surface of HOPG (free from defects), 8 9 -10 cm s -1 on reduced graphene oxide, 78 13.5 ± 2 cm s -1 on Au and 17.0 ± 0.9 cm s -1 on Pt. 103 This similarity in values is especially striking in view of the large difference in DOS, electronic structure and the different electrode configurations studied experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…15,18,20,[22][23][24] Significantly, GO has abundant oxygen functional groups, including hydroxyl, epoxy, carbonyl, and carboxyl groups. 25 The effect of GO can be modulated by modification of its oxygen moieties as well as altering chemical functionality on graphene layers. 25 Some studies suggest that GO promotes differentiation of neural stem cells and neural outgrowth.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] An interesting approach for observing the electrochemical properties of catalytic NPs is to monitor their impact (or landing) from solution onto a collector electrode, as introduced by Bard et al, 4,5 and developed by several groups. [6][7][8][9][10][11][12] In order to resolve such impacts, the use of a small-sized ultramicroelectrode (UME) is mandatory to reduce both background currents and the impact frequency.…”
mentioning
confidence: 99%